The Effect of Public Service Quality on Taxpayer Satisfaction In Online Payment of Regional Taxes - Lukieto Cahyadi (Institute of Computer Science (IOCS), 2021)
This research was conducted at the Office of the Regional Financial Management Agency for Revenue and Assets in the City of Tebinggi Tinggi. It can be seen that the amount of adjusted R square value is 0.435 or 43.5% This shows that the Service Quality Variable (X) and can explain the Customer Satisfaction Variable (Y) is 43.5%, the remaining 56.5% (100 % - 43.5%) is explained by other variables outside of this research model. (2) The results of the t-test (partial) can be seen that the obtained tcount value is 6.289 With = 5%, ttable (5%; 51-2 = 49) obtained ttable value of 1.676 From the description it can be seen that tcount (6.289) > ttable (1.676), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Product Quality Variable (X ) has a significant effect on the Customer Satisfaction Variable (Y).